MORPHOLOGICAL AND HISTOCHEMICAL CHANGES IN THE THYROID AND INTER-RENAL CELLS DURING BREEDING AND NON-BREEDING PERIODS OF CHANNA GACHUA (HAMILTON) - Mishra, S K (Indian Journal of Fisheries, 2011)
Thyroid and interrenal cells of Channagachua exhibit cyclic histological and histochemical changes duringvarious phases of annual ovarian cycle revealing their inactivity and hyperactivity during non-breedingand breeding periods respectively. There is a direct correlation between the cyclic activity in the ovariesand the cyclic activity in the interrenal cells and thyroid